Small Molecule NF-κB Inhibitors as Immune Potentiators for Enhancement of Vaccine Adjuvants - Moser, Brittany A.; Escalante-Buendia, Yoseline; Steinhardt, Rachel C.; Rosenberger, Matthew G.; Cassaidy, Britteny J.; Naorem, Nihesh; Chon, Alfred C.; Nguyen, Minh H.; Tran, Ngoctran T.; Esser-Kahn, Aaron P. (Frontiers in Immunology, 2020)
Adjuvants are added to vaccines to enhance the immune response and provide increased protection against disease. In the last decade, hundreds of synthetic immune adjuvants have been created, but many induce undesirable levels of proinflammatory cytokines including TNF- and IL-6. Here we present small molecule NF-B inhibitors that can be used in combination with an immune adjuvant to both decrease markers associated with poor tolerability and improve the protective response of vaccination. Additionally, we synthesize a library of honokiol derivatives identifying several promising candidates for use in vaccine formulations.